1997
DOI: 10.1159/000310823
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Phaco-Emulsification-Aspiration and Intra-Ocular Lens Implantation on the Pupil: Pupillographic and Pharmacologic Study

Abstract: The authors report postoperative change in pupil diameter and pupil dynamics after phaco-emulsification-aspiration and intra-ocular lens implantation by comparing the operated eye and non-operated eye in 20 patients who received unilateral surgery. Miosis was noted in the operated eye throughout the postoperative period in the dark, and also in the light at an early stage after the operation. Both the maximal constriction velocity and maximal dilatation velocity of the light reflex decreased postoperatively, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…The reported transient miotic effect of cataract surgery on short term is consistent with one previous study (Hayashi & Hayashi 2004). Yet, other studies have reported decreased pupil size up to 12 months after surgery (Komatsu et al 1997;Moller et al 2000;Kanellopoulos & Asimellis 2014). This may be caused by different levels of inflammation, as postoperative inflammation has been shown to vary similarly.…”
Section: Referencesmentioning
confidence: 94%
“…The reported transient miotic effect of cataract surgery on short term is consistent with one previous study (Hayashi & Hayashi 2004). Yet, other studies have reported decreased pupil size up to 12 months after surgery (Komatsu et al 1997;Moller et al 2000;Kanellopoulos & Asimellis 2014). This may be caused by different levels of inflammation, as postoperative inflammation has been shown to vary similarly.…”
Section: Referencesmentioning
confidence: 94%
“…men and women) are analyzed, our findings are consistent with many other studies that have reported a decrease in pupil diameter after cataract surgery. 1 , 2 , 3 , 10 , 11 , 12 , 13 , 14 , 15 , 16 In particular, we have found that the average photopic pupil suffered a slight reduction of −0.07 mm (−2.4%) and the average mesopic pupil a larger reduction of −0.44 mm (−9.6%) ( Table 2 ). The effect size reached by the mesopic pupils (Cohen's d = 1.1) is interpreted as a substantial clinical change.…”
Section: Discussionmentioning
confidence: 81%
“…Potential mechanisms of iris thinning during routine phacoemulsification include direct trauma from the phaco probe and indirect damage to iris structures from the cavitation energy generated by the phaco tip [49]. While the exact effects of mechanical phacoemulsification energy on iris stroma are unknown, existing literature suggests that on a histopathological level, phaco-generated ultrasonic waves induce intracytoplasmic vacuolation within the sphincter and dilator muscles of both human and simian irises [50,51]. Our data indicates that these post-op changes may decrease the extent of pupil dilation in the dark, pointing to reduced iris movement in dark conditions and therefore potentially reduced incidence of iris-trabecular meshwork apposition.…”
Section: Discussionmentioning
confidence: 99%